The burden of liver cirrhosis in mortality: Results from the global burden of disease study - Ye, Fei; Zhai, Mimi; Long, Jianhai; Gong, Yi; Ren, Chutong; Zhang, Dan; Lin, Xiang; Liu, Sushun (Frontiers in Public Health, 2022)
Background: Liver cirrhosis-related death is a serious threat worldwide. Number of studies exploring the mortality trend of cirrhosis caused by specific etiologies was limited. This study aimed to demonstrate the pattern and trend based on the data of Global burden of disease (GBD). Methods: The data of cirrhosis mortality was collected from the GBD 2017. The Age standardized mortality rate (ASR) and estimated annual percentage changes (EAPC) were used to estimate the temporal trend of liver cirrhosis mortality by etiologies, regions, socio-demographic index (SDI) and sexes. Results: Globally, mortality cases of cirrhosis increased 47.15%. Although the global ASR of cirrhosis mortality remained stable during this period, the temporal trend varied in etiologies. The ASR of mortality caused by hepatitis C virus (HCV), alcohol consumption and non-alcoholic steatohepatitis (NASH) increased with an EAPC of 0.17 (95% CI 0.14-0.20), 0.20 (95% CI 0.16-0.24), 1.00 (95% CI 0.97-1.04), respectively. A decrease trend of ASR was found among the causes of hepatitis B virus (BV) and other causes. The increase pattern was heterogeneous worldwide. The most pronounced increase trend was found in middle-high SDI regions and Eastern Europe. Contrary, the most pronounced decrease trend was found in low SDI regions and Western Sub-Saharan Africa. Conclusions: Cirrhosis is still a public health problem. The growth trend of cirrhosis mortality caused by HCV slowed by promoting direct-acting antiviral therapy. Unfortunately, we observed an unfavorable trend in etiologies for alcohol consumption and NASH, which indicated that more targeted and specific strategies should be established to limit alcohol consumption and promote healthy lifestyles in high-risk countries, especially in middle-high SDI regions and Eastern Europe.